Meigs syndrome, pseudo-Meigs syndrome, or pseudo-pseudo Meigs syndrome? A case report - Azie Jumaatul Adawiyah Nabir; Chiew Yee Lau; Adilah W. Ab Rahim; Aliyyah Mohammad Khuzaini (Elsevier, 2024)
Background: Meigs syndrome, pseudo-Meigs syndrome, and pseudo-pseudo-Meigs syndrome showcase a diagnostic challenge in the management of complex pediatric cases. Case report: We report a case of a 6-year-old girl who presented with progressive breathlessness, lethargy, and constipation for two weeks, associated with multiple episodes of joint pain and polymorphous rash. Imaging of the thorax, abdomen, and pelvis suggested bilateral pleural effusion, ascites, and an ovarian mass with abdominal involvement. The pleural and peritoneal fluids were exudative in nature. Unfortunately, she was not fit for a biopsy of the mass and was treated in the intensive care unit for one month. She was initiated on oral corticosteroids for suspicion of an underlying auto-inflammatory disease. However, subsequent investigations yielded inconclusive results. She gradually recovered and was well for a year. She presented again with constitutional symptoms and was diagnosed with diffuse large B-cell lymphoma (DLBCL). Thus, it was retrospectively apparent that this was a case of pseudo-Meigs syndrome. Conclusion: We describe an unusual presentation of DLBCL with a temporary resolution of symptoms.